Pattern of Clinical Presentation, Staging and Surgical Treatment of Lung cancer in 250 Consecutive Patients. - Tiwari, Manoj; Thakur, Binay; Shun, Zhenqing; Khatiwada, Sagar; Shrestha, Shashank; Kharel, Ashish; Adhikari , Mahesh Mani; Bhattarai, Sachee (Nepalese Journal of Cancer, 2024)
Introduction: GLOBOCAN 2022 showed lung cancer to be leading cancer in Nepal accounting for about 11% (2431) of all new cancer cases and about 15% (2207) of all cancer deaths. We reviewed the pattern, clinical presentation, stage and multimodality treatment of lung cancer results in Nepal. Methods: Two hundred fifty consecutive patients with clinical stages of I-IIIA, who were considered for lung resectional surgery were studied. Bronchoscopy and Computed Tomography were used for diagnosis and staging. Results: Surgery alone was done in 36% cases, rest of the patients (64%) underwent multimodality approach. Lobectomy, bilobectomy, pneumonectomy, sub lobar resection and sleeve resection were done in 85.6%, 4%, 6.4%, 2% and 2% respectively. Final histology revealed squamous cell carcinoma, adeno carcinoma, and others in 72.4%, 18.4%, 9.2% respectively. Final pathological report showed stage I, II, and III in 14.8%, 30% and 55.2% cases. Thirty-day mortality was observed in 1.6% of cases. Air leak was most common post operative complication (8.4%). Conclusion: Squamous cell carcinoma still remains the commonest pathological variant of lung cancer in Nepal. Lobectomy remains the most commonly performed surgical procedure